X (Twitter) in the university context: Functions, forms and disciplinary variations of research tweets - Claire Kloppmann-Lambert; Shirley Carter-Thomas (Ibérica)
Research dissemination has recently undergone a profound transformation with the advent of numerous new digital genres. Some researchers now present and promote their research through academic tweets, conference tweets, and tweetorials, but little is known about how universities, in turn, communicate about this research on X (or Twitter).